EPIDEMIOLOGICAL ASPECTS OF POLYGLANDULAR AUTOIMMUNE SYNDROME TYPE II IN A GROUP OF ADULTS WITH THYROID DISEASES AND DIABETES MELLITUS - Adriana, Gherbon (European Scientific Journal, ESJ, 2014)
Background&Aims: Polyglandular autoimmune syndrome (PAS) type II is the most common of the immunoendocrinopathy syndromes. It is characterized by the presence of autoimmune Addison disease in combination with thyroid autoimmune diseases, type 1 diabetes mellitus, primary hypogonadism, myasthenia gravis, and celiac disease. The purpose of this study is to determine the epidemiological aspects of PAS type II in a group of adults with thyroid diseases and diabetes mellitus (DM). Methods: The studied group was of 350 cases with an age between 18-79 years. The group of adults was subdivided according to the type of changes in the glycemic balance in 2 subgroups: DM type 1 represented by 60 cases (17.14%) and DM type 2 represented by 290 cases (82.86%). The methods of investigation were represented by clinical, imaging, biochemical, hormonal and immunological parameters. Results: The prevalence of PAS type II in the study group was 3.14% (100% F and 0% M, p<0.001, X2=11.18) and prevailed in middle – age women. PAS type II prevalence in DM type 1 was 11.66% and 1.38% in DM type 2 (p<0.001, X2=200.01). Conclusions: PAS type II has prevailed in females and in the group with DM type 1 due to autoimmune origin.